Business Model: Literature Review - Afzal Sayed Munna (PINISI Discretion Review, 2021)
The term Business Model has been in use for many years which is a scientific method of being creative and innovative in creating successful business. The aim of this literature review is to define the theory relating to the business model (which includes various definitions from business and economic perspectives) and create a real-life analytical tool to define the characteristics of each part of business model, i.e., customers, distribution, value, resources, activities, cost and revenue.